Prophylaxis of thromboembolic complications in patients undergoing orthopedic surgery - Małek, Anna; Wysokińska, Olga; Żyga, Justyna; Iwaniszyn-Zapołoch, Klara; Zadrożna, Karolina (Journal of Education, Health and Sport, 2022)
Venous thromboembolism is undoubtedly one of the frequent and dangerous complications after orthopedic surgery. If not detected in time, it can lead to very serious consequences concerning the patient’s health and life. Therefore, it is crucial to know the risk factors for thromboembolic incidents. Among these factors, we can distinguish those related to the patient, his or her health status, lifestyle and factors that depend on the type of orthopedic intervention performed. Each patient should undergo an individual assessment of risk factors before undergoing surgery. Undoubtedly, an important role is played by observing the patient to detect early and late symptoms, as well as appropriate care in the postoperative period to reduce the risk of thromboembolic incidents. It is important to catch the disease at an early stage and undertake appropriate diagnostics to exclude or confirm the disease. The risk of venous thromboembolism can be lowered by using thromboprophylaxis. Various forms of prevention are available, which include various methods and means of prevention. An appropriate approach to the problem of the occurrence of this type of complication after orthopedic surgery affects not only the results of the treatment of orthopedic conditions, but also the overall health and functioning of the patient and his prognosis.